Juridical Analysis of Multiple Issuance of Non-Dispute Statements by the Previous Village Head and Current Village Head against Different Applicants for Applications for Land Rights - Panji, Dikia Satrio (Jurnal Konstatering, 2022)
The practice of persons who are not responsible for Issuing multiple Statements of No Dispute issued by Village Office Officials which can harm materially and non-materially to land rights holders. This study aims to analyze juridically the issuance of multiple Non-Dispute Statements made by Village Heads who have different terms of office, the mechanism for applying for land ownership rights in the City of Semarang. The research approach method used in this thesis is to use the sociological juridical legal research method. The specifications of this research are using descriptive analysis. The type of data used in this study is primary data which includesThe 1945 Constitution, the Basic Agrarian Act No. 5 of 1960, Government Regulation Number 24 of 1997, as well as secondary data containing books and supporting documents or library materials. The data analysis method used in analyzing the data is a qualitative analysis of the interaction model as proposed by Miles and Huberman. The results of the study show that: First, Issuance of a Statement of No Dispute has a procedure for challenging provisions, requirements that must be carried out from the time the applicant's application is submitted until the issuance of a Statement of No Dispute which gets approval from the Village Head and District Head. Second, legal protection for the aggrieved party from the issuance of multiple non-dispute statements.Keywords: Letter; Dispute; Statement; Village.